2017
DOI: 10.1111/ocr.12190
|View full text |Cite
|
Sign up to set email alerts
|

Lithium enhances alveolar bone formation during orthodontic retention in rats

Abstract: LiCl enhances alveolar bone formation during orthodontic retention in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In support of these findings, previous investigations have demonstrated potential benefits of lithium chloride on fracture healing (26,27) and alveolar bone repair (16)(17)(18)(19)(20)(21). Han et al (16) demonstrated that local administration of lithium chloride stimulated greater alveolar bone volume and mineral density during the healing of surgicallycreated periodontal defects in estrogen-sufficient rats.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In support of these findings, previous investigations have demonstrated potential benefits of lithium chloride on fracture healing (26,27) and alveolar bone repair (16)(17)(18)(19)(20)(21). Han et al (16) demonstrated that local administration of lithium chloride stimulated greater alveolar bone volume and mineral density during the healing of surgicallycreated periodontal defects in estrogen-sufficient rats.…”
Section: Discussionmentioning
confidence: 76%
“…Pre-clinical dental studies have shown benefits of lithium chloride, in states of both estrogen sufficiency and deficiency, on bone formation during orthodontic retention, midpalatal expansion and surgically-created periodontal defects, for improving implant osseointegration and for the attenuation of bone loss in a model of induced periodontitis (15)(16)(17)(18)(19)(20). A single previous study in estrogen-sufficient rats evaluated the effects of lithium chloride on the healing process of tooth sockets.…”
Section: Introductionmentioning
confidence: 99%
“…LiCl promotes implant osseointegration and osteogenesis in osteoporotic rats [28,29]. LiCl treatment increased the alveolar bone mass during orthodontic retention [30]. Combination of LiCl and LY294002 increased osteoblastic differentiation but decreased osteoclast differentiation [31].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting and unusual element adopted as inorganic components in the functionalization was lithium: after an initial observation of beneficial effect on bone status in patients undergoing lithium therapy for mental disorders, lithium proved to promote osteogenic differentiation, via activation of the Wnt signalling pathway, inhibiting glycogen synthase kinase-3beta (GSK-3β) [85].…”
Section: Discussionmentioning
confidence: 99%